Acromegaly due to pituitary macroadenoma in a patient with McCune-Albright syndrome. Case report and literature overview - Alcalde-Loyola, Carlos (2022)
Background: McCune-Albright syndrome (MAS) is a rare disease characterized by the triad: café-au-lait skin spots, polyostotic fibrous dysplasia, and precocious puberty. It can affect various hormonal axes, including growth hormone (GH), and may be associated with acromegaly. Case report : We describe the case of a 44-year-old woman with peripheral precocious puberty, abnormal uterine bleeding, growth of the hands and feet, prognathism, frontal prominence, café-au-lait spots, and stony tumors on the face and forearms. Results: Supported by laboratory and imaging tests, the diagnoses of acromegaly, hypogonadotropic hypogonadism and McCune-Albright syndrome were reached. The patient underwent surgical treatment with persistence of clinical and laboratory disease. Conclusion: Timely diagnosis and treatment of acromegaly and its complications will provide a better prognosis for patients with MAS.